Agricultural trade policies and trade relations in transition economies - Angela Bergschmidt; Monika Hartmann (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 1998)
The economic changes during transition involved a shift away from the planned foreign trade organization within the council for mutual economic assistance. Following a phase of farreaching trade policy liberalization, the agricultural sector in the Central and Eastern European countries (CEEC) has in the last years again been increasingly regulated. At the same time as the CEECs are striving for accession to the European Union, regional free trade agreements (FTA) and membership in the World Trade Organization (WTO) have gained importance. The analysis shows that an effective reduction of agricultural protectionism as a result of WTO obligations can only be expected from a small number of CEECs. The effects induced through changes in international agricultural commodity markets in the CEECs depend particularly on the trade status and the trade structure in the agricultural sector, as well as on internal macro- and agricultural economic distortions. An appraisal of regional FTAs such as the Central European Free Trade Agreement and the Baltic Free Trade Agreement has to take into consideration the Vinerian effects of trade creation and trade diversion, as well as non-traditional effects, such as an increase in credibility of political decisions, and the strengthening of the bargaining power of the countries involved. The Europe Agreements and the aim of accession to the EU are of crucial importance to the CEECs. In the framework of an empirical analysis it is shown that the countries which have not been invited to the first round of accession negotiations might be adversely affected by the first east enlargement of the EU. – – Die wirtschaftlichen Veränderungen während der Transformationsphase beinhalten eine Abkehr von der planwirtschaftlichen Organisation des Außenhandels innerhalb des Rates für Gegenseitige Wirtschaftshilfe. Nach einer Phase weitgehender Liberalisierung von Handelspolitiken in den Ländern Mittel- und Osteuropas wurde in den letzten Jahren wieder verstärkt regulierend in den Agrarsektor eingegriffen. Gleichzeitig gewinnen neben dem angestrebten Beitritt in die Europäische Union regionale Freihandelsabkommen sowie die Mitgliedschaft in der Welthandelsorganisation (WTO) zunehmend an Bedeutung. Die Analyse zeigt, daß eine effektive Reduzierung der Agrarprotektion aufgrund der eingegangenen WTO-Verpflichtungen nur von wenigen mittel- und osteuropäischen Ländern (MOEL) zu erwarten ist. Die über die internationalen Agrarmärkte induzierten Effekte in den MOEL hängen insbesondere von dem Handelsstatus und der Handelsstruktur im Agrarsektor sowie den internen agrar- und makroökonomischen Verzerrungen ab. Eine Bewertung regionaler Handelsabkommen wie des Central European Free Trade Agreement und des Baltic Free Trade Agreement muß neben den traditionellen Effekten, wie dem der Handelsschaffung und der Handelsumlenkung, auch die nicht-traditionellen Effekte, wie die durch die Abkommen induzierte Erhöhung der Glaubwürdigkeit politischer Entscheidungen und der Stärkung der Verhandlungsmacht dieser Länder mit einbeziehen. Die mit der EU abgeschlossenen Europa-Abkommen als auch der angestrebte Beitritt zur EU ist von herausragender Bedeutung für die MOEL. Im Rahmen einer empirischen Analyse wird aber auch gezeigt, daß die Länder, die zunächst nicht eingeladen werden, der EU beizutreten, negativ von der ersten Erweiterungsrunde betroffen sind.
urn:nbn:de:gbv:3:2-22720
Keywords: 330; Agraraußenhandel; Außenhandelspolitik; WTO-Regeln; Internationale Wirtschaftsbeziehungen; EU-Erweiterung; Osteuropa